Modularidad e innatismo: una crítica a la noción sustancial de módulo - Skidelsky, Liza (Revista de Filosofía, 2007)
In the Philosophy of Cognitive Science, it is a common held view that the modularity hypothesis for cognitive mechanisms and the innateness hypothesis for mental contents are conceptually independent. In this paper I distinguish between substantial and deflationist modularity as well as between substantial and deflationist innatism, and I analyze whether the conceptual independence between substantial modularity and innatism holds. My conclusion will be that if what is taken into account are the essential properties of the substantial modules, i.e. domain specificity and informational encapsulation, then it seems to be such independence. However, if what is taken into account is the function of the substantial modules, then it seems to be a conceptual connection from modularity to substantial innateness.